Adsorção de fármacos utilizando resíduos siderúrgicos ricos em óxido de ferro como materiais adsorventes - Duarte, Iara Jennifer Moura (2024)
Pharmaceuticals are emerging contaminants of great concern due to their adverse effects on living organisms. Furthermore, conventional processes for treating these pollutants are inefficient. In light of this issue, this study proposes the use of steel wastes rich in iron oxides as alternative adsorbents for the adsorption of the pharmaceuticals amoxicillin (AMX), caffeine (CFN), ciprofloxacin (CIP), and diclofenac (DCF). For the affinity tests, six steel wastes were used: dust from the electrostatic precipitator (I); scale from the plate mill (II); dust from the Linz and Donawitz converter (III); dust from the blast furnace collector (IV); dust from the blast furnace cast house dedusting system (V); and dust from the Kanbara reactor dedusting system (VI). The adsorption tests revealed that steel wastes II and IV showed greater selectivity for ciprofloxacin, while waste VI had higher selectivity for caffeine. For the determination of caffeine and ciprofloxacin in effluents using spectrometric techniques, methods of molecular absorption spectroscopy in the ultraviolet and visible (UV-vis) regions were developed and validated. As a result, the adsorption tests were performed at pH 7 and at wavelengths of 273 nm for CFN and CIP. The results demonstrated that there is no matrix effect when comparing the slope of the analytical curves (with and without environmental matrix). Considering the figures of merit, the developed and validated methods proved to be efficient for the quantification of the evaluated pharmaceuticals. In the CFN adsorption test using material VI, equilibrium was reached after 96 hours of contact between the adsorbent and adsorbate, with removal rates of 84.00%, 81.09%, and 73.19% for initial concentrations of 10 mg L−1, 20 mg L−1, and 30 mg L−1 of caffeine, respectively. The pseudo-first-order model best described the experimental behavior. The values of Gibbs free energy change (ΔG°) were negative, indicating that the adsorption process is feasible and spontaneous. For the CIP adsorption test using wastes II and IV, the kinetics followed the pseudo-first-order rate equation. The maximum adsorption capacity for CIP, based on the Sips model, was 41.85 mg g−1 at a temperature of 45°C. Finally, the best adsorbent materials were impregnated with sawdust residue (BCS500) to improve the surface area of the steel wastes (IIC500, IVC500, and VIC500). The best BET surface area value was obtained for BCS500 (SBET = 187 m2 g−1). Therefore, the use of steel wastes as adsorbents stands out as a promising strategy in the search for innovative solutions to address the issue of emerging compounds in aquatic environments.